Plant Disease Control by Non-Thermal Atmospheric-Pressure Plasma - Adhikari, Bhawana; Pangomm, Kamonporn; Veerana, Mayura; Mitra, Sarmistha; Park, Gyungsoon (Frontiers in Plant Science, 2020)
Disease stresses caused by pathogenic microorganisms have currently increased probably because of global warming. Conventional technologies for plant disease control have often revealed their limitations in efficiency, environmental safety, and economic costs. The improvement in efficiency and safety is highly demanded. Non-thermal atmospheric-pressure plasma has demonstrated its potential as an alternative tool for efficient and environmentally safe control of plant pathogenic microorganisms in many studies, which are overviewed in this review. Efficient inactivation of phytopathogenic bacterial and fungal cells by various plasma sources under laboratory conditions has been frequently reported. In addition, plasma-treated water shows antimicrobial activity. Plasma and plasma-treated water exhibit a broad spectrum of efficiency in the decontamination and disinfection of plants, fruits, and seeds, indicating that the outcomes of plasma treatment can be significantly influenced by the microenvironments between plasma and plant tissues, such as surface structures and properties, antioxidant systems, and surface chemistry of plants. More intense studies are required on the efficiency of decontamination and disinfection and underlying mechanisms. Recently, the induction of plant tolerance or resistance to pathogens by plasma (so called “plasma vaccination”) is emerging as a new area of study, with active research going on this field.